Temporary Team Performance and Knowledge Hiding: Mediated by Interpersonal Mistrust - Miao, Yurong; Ye, Suyang; Chen, Min (Frontiers in Psychology, 2022)
Although scholars have acknowledged that knowledge hiding is negatively with team performance, none of the extant research has revealed the relationship between knowledge hiding and the performance of temporary teams. To fill this gap, we will explore whether and how knowledge hiding influences temporary team performance. Following a literature review, the correlation between knowledge hiding, interpersonal distrust, and temporary team performance is explored, and the theoretical model between variables is constructed, along with four hypotheses. Then, a quantitative analysis is conducted through a QS (Questionnaire Survey) design on the proposed hypotheses. Specifically, test is conducted on the collected data, and then SPSS and AMOS are used to integrate and analyze the data of 102 teams. The results show that knowledge hiding and its two dimensions (active and passive hiding) have a negative impact on the work efficiency of temporary teams. Interpersonal distrust plays a mediating role between knowledge hiding and temporary team performance. The incentive atmosphere, including control atmosphere and performance atmosphere, can regulate the performance of a temporary team efficiently. Control atmosphere is favorable to improving interpersonal trust and team performance, and performance atmosphere is inverted U-shaped regulation between interpersonal distrust and temporary team performance. Based on the above conclusions, the corresponding management suggestions that encouraging members in temporary teams to share actively and confronting the passive concealment of knowledge are put forward to enhance interpersonal trust and improve the efficiency of the temporary team.